2009
DOI: 10.26719/2009.15.1.65
|View full text |Cite
|
Sign up to set email alerts
|

National survey of Prevalence of Mental Disorders in Egypt: preliminary survey

Abstract: Enquête nationale sur la prévalence des troubles mentaux en Égypte : étude préliminaire RÉSUMÉ Cette étude constitue une première étape de l'enquête nationale sur la prévalence des troubles mentaux en Égypte. Nous avons réalisé une enquête auprès des ménages par porte à porte dans cinq régions d'Égypte et avons interrogé 14 640 adultes âgés de 18 à 64 ans. Les troubles mentaux ont été diagnostiqués sur la base de l'interrogatoire MINI-Plus. La prévalence globale a été estimée à 16,93 % de la population adulte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 18 publications
12
84
5
Order By: Relevance
“…In the same line the result was consistent with the results of previous study [21] showed that, the majority of studied sample were single and referred their results to poor social adjustment as a well-known major symptoms of schizophrenia, on the contrary the results of the current study was inconsistent with the findings of others [26] indicated that, more than half of the studied sample was married. In the same direction, authors [27] high lighted the role of marital status (widowed, divorced/separated) as risk factor for recurrent mental illness, therefore marital status might not have a significant effect on patient social skills.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line the result was consistent with the results of previous study [21] showed that, the majority of studied sample were single and referred their results to poor social adjustment as a well-known major symptoms of schizophrenia, on the contrary the results of the current study was inconsistent with the findings of others [26] indicated that, more than half of the studied sample was married. In the same direction, authors [27] high lighted the role of marital status (widowed, divorced/separated) as risk factor for recurrent mental illness, therefore marital status might not have a significant effect on patient social skills.…”
Section: Discussionmentioning
confidence: 99%
“…A transformation of the mental health care system towards a multidisciplinary, coordinated and holistic approach is required. It should be noted, however, there have been several recent reports on mental health in the Arab countries [43][44][45][46][47][48][49][50][51][52][53][54][55]. This trend highlights a change in attitudes among health professionals as well as the public concerning mental health and wellness.…”
Section: Coordination Of Carementioning
confidence: 99%
“…Mood disorders were the commonest (6.43%), followed by anxiety disorders (4.75%) and multiple disorders (4.72%). The prevalence of psychosis was around 0.2%, which is slightly lower than is commonly reported worldwide (Ghanem et al, 2009). …”
Section: Epidemiologymentioning
confidence: 76%
“…Despite the interest in attention-deficit hyperactivity disorder (ADHD), the recent National Survey of the Prevalence of Mental Disorder excluded symptoms of ADHD at its first stage (Ghanem et al, 2009). Pervasive developmental disorders are mostly seen by paediatricians rather than psychiatrists.…”
Section: Profile Of Psychiatric Presentationmentioning
confidence: 99%